KETERAMPILAN KOMPUTER DALAM SELEKSI PENGISIAN PERANGKAT DESA BESOLE - Atmoko, Agus Dwi; Suryadin, Iman Tri (ABDI WINA JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The filling of the vacancies for the service section head and the government section head in Besole Village, Bayan District, Purworejo Regency was carried out in three stages, namely a basic ability test (TKD), a speech test, and a Computer Skills Test. Sawunggalih Aji Polytechnic became the institution appointed to administer the test. The TKDA test consists of 100 multiple choice questions, and is continued with speech skills and the computer skills test consists of three sessions. The session is Ms Word skills, Ms skills. Excel and Ms. Power point. The three scores are then totaled and ranked. From the test results it was stated that all participants were able to complete the three stages of the test quite well. The three test were carried out smoothly and without a hitch